In Situ Ultrasonic Measurements as a Tool to Characterize the Stages of the Zeolite A Crystallization Process - Baser, Hasan-Hüseyin; Thangaraj, Selvam; Schwieger, Wilhelm; Hartmann, Martin (Chemie Ingenieur Technik, 2023)
Zeolite A (LTA) was synthesized at 80 °C under hydrothermal conditions from a gel with the molar composition of 2.5 Na2O : 2 SiO2 : Al2O3 : 80 H2O. In the present study, we report the use of home-made ultrasound devices as a real-time, in situ diagnostic tool for monitoring the progress of zeolite formation. In addition, the specific aim of this study was to show that the measured ultrasound parameters – ultrasonic (US) velocity and attenuation – simultaneously provide independent information about the changes in the liquid and solid phase, respectively, during the crystallization process. Both views are necessary for extracting kinetic data about the zeolite crystallization processes and allow elucidating the different stages of zeolite LTA formation process. The obtained in situ US data were compared with conventional ex situ powder X-ray diffraction measurements following the formation of zeolite LTA from dense gels. The results demonstrate that a good correlation exists between the crystallization progress of zeolite LTA in terms of crystallinity changes and the ultrasonic attenuation and velocity.
CRIS-Team Scopus Importer:2024-12-16
Keywords: In situ monitoring; Synthesis of zeolite LTA; Ultrasonic attenuation and velocity